2016
DOI: 10.3390/rs8080657
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Clearances in Tropical Dry Forests Using Breakpoints, Trend, and Seasonal Components from MODIS Time Series: Does Forest Type Matter?

Abstract: Tropical environments present a unique challenge for optical time series analysis, primarily owing to fragmented data availability, persistent cloud cover and atmospheric aerosols. Additionally, little is known of whether the performance of time series change detection is affected by diverse forest types found in tropical dry regions. In this paper, we develop a methodology for mapping forest clearing in Southeast Asia using a study region characterised by heterogeneous forest types. Moderate Resolution Imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 84 publications
3
33
3
Order By: Relevance
“…using only a selection of MODIS bands that are most relevant for a specific classification problem). Grogan et al (2016) showed that such a reduction of the featurespace affects classification accuracies only marginally but improves computational time, while other researchers obtained similar accuracies even by reducing the number of sample points (Pal, 2006).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…using only a selection of MODIS bands that are most relevant for a specific classification problem). Grogan et al (2016) showed that such a reduction of the featurespace affects classification accuracies only marginally but improves computational time, while other researchers obtained similar accuracies even by reducing the number of sample points (Pal, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…shifting cultivation, rubber) and more recent studies, focusing on a broader range of dynamics and processes to determine vegetation and land-use phenology, have emphasized the importance of including band 7 (Shortwave Infrared (SWIR)) to improve the mapping accuracy of forest dynamics (Grogan, Pflugmacher, Hostert, Verbesselt, & Fensholt, 2016;Hurni, Hett, Heinimann, Messerli, & Wiesmann, 2013;Z. Li & Fox, 2012;Suepa et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…BFAST is a widely used method for detecting trend and seasonal breaks in time series. It has mainly been applied to monitoring forest disturbance (e.g., [13,19,20]) but has also been applied to more general land cover monitoring scenarios (e.g., [21][22][23]). BFAST uses an iterative process to find both trend and seasonal changes across a whole time series [15].…”
Section: Bfastmentioning
confidence: 99%
“…(2) 15 −30 20 −37 25 −43 30 −49 Here, the SOS has been moved forward by 37 days by changing the c 1 parameter from 5 to 25.…”
Section: Simulating Seasonal Time Seriesmentioning
confidence: 99%
“…Since the first overviews regarding change detection in the 1960s [3], many works in this discipline have been conducted using remote sensing data. Among the recent works, we can cite the monitoring of arid environments [4], shorelines [5] and forests or woodlands [6][7][8][9] as well as detection of urban expansion [10], changes in buildings structure [11], changes in submerged sea grass biomass [12], mapping of landslides [13], damage to cultural heritage sites [14] and the proposition of new methodologies [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%